Speaking sentences : inside women's experiences of gender, punishment and rehabilitation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Policy, Massey University - Caird, Bridget (Massey University, 1999)
This thesis explores the ways in which gender, punishment and rehabilitation shape women's experience of imprisonment in New Zealand. In particular, it seeks to expose tensions between punitive and rehabilitative regimes within women inmates' lives and critically addresses the role of gender within these variables. The thesis is a qualitative venture in an area characterized by a dearth of empirical data specific to women's needs as prisoners. Literature and research from overseas, and a smaller amount from New Zealand, highlight relevant theoretical areas and important issues in women's imprisonment, which in turn provide background for the navigation of sixteen women's experiences in two prisons. The research also forges some junctions between the restructuring of the New Zealand state sector upon prison operations, and women's experience of prison. Accordingly, it establishes links between gender, punishment and rehabilitation, and the current prison managerial environment to identify areas for change women highlight as central to their wellbeing as prisoners. The research finds that historically, gender has held the strongest influence over the institutional treatment of women prisoners. As a cultural and social process that assigns less value to women, gender continues to play a central role in their experience of both punishment and rehabilitation today. Attention is drawn to women prisoners' experience of punishment as characterized by more than the official deprivation of liberty alone but as an area of numerous additional punishments, both official and unofficial, and which are frequently arbitrary or discretionary in nature. These span the administration of privilege and punishment, to health care, sexuality, work, rehabilitation and recreation. Rehabilitation is described by the inmates as a process of compliance and superficial change where 'curative' efforts inadvertently become aspects of coercion, due to the overriding prison culture of discipline and control. Accordingly, due to conflicting objectives between punitive and rehabilitative regimes within prisons, the worth of rehabilitation in the prison context is exposed as inherently problematic. Whilst a tension between punishment and rehabilitation in prisons precedes recent structural and managerial changes to New Zealand prisons, the role of neo classical economic priorities within prison management today appears to have brought it into sharper focus. Accordingly, a traditional lack of attention to important variables such as gender and power within women's prisons, converges with the current emphasis upon quantitative standards for prison management, over attention to important qualitative features of imprisoned women's experience. Conclusively, central empirical features of women's imprisonment and their ensuing needs for sex equity, adequate health care, fair treatment, and work and recreational opportunities that oppose gender constraints and pay attention to stereotypical perceptions of women, are brought to the fore within New Zealand's current prison policy climate. The study provides a guiding canvas for future policy development to pay attention to the junctions between punishment, rehabilitation and gender in women's prisons, for more appropriate responses to women inmates needs.
Keywords: Women prisoner rehabilitation; Women's prisons, New Zealand; Women prisoners; Punishment and rehabilitation, New Zealand